Brain Gymnastic Decreases Dementia Levels in the Elderly - Sahrul Widyastuti; Budi Widiyanto; Arwani Arwani (Poltekkes Kemenkes Semarang, 2020)
Background: Dementia (senility) is a condition where somebody examine the decrease in memory and thinking ability, and this ability causing daily life disorder. The number of elderly who has dementia from year by year showed an increase. Dementia that is not treated properly will get worse to Alzheimer's. However, until now there has been no research that shows in what age range brain exercise has an effect or impact to reduce the level of dementia in the elderly.Purpose: To analyze the effect of brain gymnastics on decreasing the level of dementia in different elderly groups.Methods: The research design was quasi experimental with non-randomized control group. The number of respondents was 45 respondents. The respondents were intervented with brain gymnastic. The instrument used was a Mini Mental State Examination (MMSE) questionnaire. Data were analised using kruskal wallis and Mann Whitney test.Results: The results of the three groups research before and after given brain gymnastics showed that there were significant changes. Old elderly make a significant difference with a p value of 0,000 (p 0.05). Mann Whitney test result obtained pre and old elderly with p value 0.001.Conclusion: Brain gymnastics affects the decrease level of dementia in different age groups of elderly.